The Use of the Flipped Classroom in Teaching English Speaking for Senior High School Students - Majidha, Anita; Novi Rahmania Aquariza; Mujad Didien Afandi; Tiyas Saputri (Universitas Islam Lamongan, 2025)
Speaking remains one of the most challenging skills for Indonesian students to master, largely due to limited opportunities for oral practice in traditional, teacher-centered classrooms. To address this issue, this study investigates the use of the Flipped Classroom model in improving students’ English-speaking competence at MA Darul Ulum Waru, Sidoarjo. Employing a qualitative descriptive design, the research was conducted over one month (April–May 2025) and involved one English teacher and fifteen eleventh-grade students. Data were collected through classroom observations, structured interviews, and documentation to explore both instructional implementation and participants’ experiences. The findings reveal that the Flipped Classroom encouraged students to prepare independently before class, resulting in more interactive in-class speaking activities. Students demonstrated greater confidence, motivation, and fluency, while the teacher reported higher engagement and participation levels. Despite challenges related to digital access and self-regulation, the approach proved effective in promoting speaking competence. This study suggests that English teachers integrate digital pre-class learning into speaking instruction and that policymakers support technology-based pedagogical innovation to foster more communicative, student-centered classrooms in Indonesian schools.